155 Audit of Functional Outcome of Mason and Molloy Type 2 Posterior Malleolar Ankle Fractures Treated with Open Reduction and Internal Fixation Using A Posterolateral Approach. (4th May 2021) - Master, A; Saad, A; George, A; Syed, A; Laing, P; Hickey, B
Abstract: Introduction: It has been shown that direct fixation of the posterior malleolus improves functional outcomes. Our aim was to audit the functional outcome of patients with these fractures which were fixed with an isolated posterolateral approach. Method: A consecutive case series of patients who underwent direct fixation of the posterior malleolus using a posterolateral approach between 20/12/2012 and 23/1/2020 was identified. Fractures were classified according to Mason and Molloy classification based on preoperative CT. Type 2a and 2b fractures were included. Functional outcome was assessed using Olerud-Molander score. Result: 18 patients were included. Mean age at time of surgery was 52 years (range 20 to 75 years). 56% (n = 10) were female. Mean follow up was 18.1 months (range 4.2 months to 7.2 years). OMAS score for type 2a fractures (n = 9) was 71.1 (95% CI 65.3 to 77.0). OMAS score for type 2b fractures (n = 9) was 67.8 (95% CI 54.6 to 81.0). There was no significant difference between groups (p = 0.65). Conclusions: Fixation of Mason and Molloy Type 2 fractures using an isolated posterolateral approach results in satisfactory functional results for the majority of patients. Further prospective comparative study is needed to identify which patients benefit most from alternative approaches.